2018
DOI: 10.3390/ijerph15081790
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Refugee Crisis on the Greek Healthcare System: A Long Road to Ithaca

Abstract: Greece is the country of “Xenios Zeus”, the Ancient Greek god of foreigners and hospitality; however, it is also the main point of entry to Europe. Since the beginning of 2014, 1,112,332 refugees crossed the borders of Greece. Overall, 33,677 children and adolescent refugees sought asylum in Greece from 2013 to 2017, while 57,042 refugees are currently being hosted. The rapid entry of refugees into Greece raised the critical issue of health policy. The Greek National Health Service (NHS) faces many challenges.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
70
0
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(88 citation statements)
references
References 77 publications
0
70
0
14
Order By: Relevance
“…Another systematic review showed differences in caesarean section rates by place of the refugee/migrant woman's origin and the host country [33]. In particular there were higher overall caesarean rates for Sub-Saharan African, Somali and South Asian women; higher emer- [36]. This massive demographic and social change to Greece's country occurs at a time of severe economic crisis [37].…”
Section: Mode Of Obstetrical Deliverymentioning
confidence: 99%
“…Another systematic review showed differences in caesarean section rates by place of the refugee/migrant woman's origin and the host country [33]. In particular there were higher overall caesarean rates for Sub-Saharan African, Somali and South Asian women; higher emer- [36]. This massive demographic and social change to Greece's country occurs at a time of severe economic crisis [37].…”
Section: Mode Of Obstetrical Deliverymentioning
confidence: 99%
“…Greece is called the country of "Xenios Zeus", the Ancient Greek god of foreigners and hospitality [1]. However, Greece has been grappling with a severe socio-economic crisis since 2009 [1].…”
Section: Introductionmentioning
confidence: 99%
“…Greece is called the country of "Xenios Zeus", the Ancient Greek god of foreigners and hospitality [1]. However, Greece has been grappling with a severe socio-economic crisis since 2009 [1]. From the period 2015-2016, Greece experienced an unprecedented influx of refugees and migrants fleeing their home countries in the Middle East because of war, which created what is now known as the most massive displacement of a people since World War II [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fragile states are major sources of mass migration leading to refugee crisis and disruption of health systems of the receiving countries [17,18]. Leaving fragile states behind will create dangerous pockets of serious infectious diseases that might affect the whole world.…”
mentioning
confidence: 99%